Penerapan Augmented Reality Sebagai Alternatif Media Pembelajaran Bahasa Inggris Pada Anak Usia Dini - Dyah Monika Ismawanti; Hari Widi Utomo; Gita Fadila Fitriana (JURIKOM (Jurnal Riset Komputer), 2021)
Learning media is a means of delivering subject matter that can channel messages, stimulate thoughts and feelings and a person's willingness to learn. This is where the need for education from an early age, which is based on Law Number 20 of 2003 concerning the National Education System, states that early childhood education is one of the coaching efforts aimed at children from birth to 6 years. Awareness of the importance of mastering foreign languages, especially English in the current information age, has led to efforts to learn these languages from an early age. Therefore, this study aims to provide an alternative solution in early childhood learning media using marker based augmented reality technology. Making this application using Unity and Vuforia. Development for this software uses the Waterfall method. By utilizing AR technology supported by animation, images and sounds can attract children's interest in learning. The results of the tests that have been carried out through black box testing and pre-test and post-test that have been carried out by the correspondent show the results that the percentage figure is 100% which can be concluded that all features can run well based on their functions. The results obtained during the pre-test get an average of 48 while the post-test results have increased by getting an average of 97.5 which shows that the alternative application of English learning media is fun and very suitable for use by users as an effective and efficient learning medium. and of course interesting